Becoming Legible to the State : The Role of Detection and Enforcement Capacity in Tax Compliance - Okunogbe, Oyebola (World Bank, Washington, DC, 2021)
Tax revenue in many low-income countries is inadequate for funding government investment in infrastructure and public services. This paper examines two dimensions of low state capacity that hinder tax collection: the inability to ascertain the tax base (detection capacity) and the inability to enforce unpaid liabilities (enforcement capacity). A randomized experiment with Liberian property owners finds that using identifying information from a newly developed property database to alert property owners that their noncompliance has been detected quadruples the tax payment rate, but only when the notice includes details on the penalties for noncompliance. A second experiment finds a further increase in compliance from signaling greater enforcement probability to delinquent property owners. These results highlight the importance of investments in both detection and enforcement capacity.